Estimation of combining ability for yield and its components traits in bread wheat (Triticum aestivum L.) by using half diallel analysis - Singh, Yash Pal; Kumar, Satish; Kumar, Sumit (Journal of Cereal Research, 2023)
Ten genotypes of bread wheat (Triticum aestivum L.) were used and their 45 F1’s from half diallel cross, and they were planted at the Agricultural Research farm ITM University, Moradabad using randomized block design with three replicates in order to study the combining ability. Significant differences were observed among the treatment (parents and their 45 F1’s) revealing that existence of variability for all the traits. The present study revealed that mean squares due to (GCA) and (SCA) were significant for all the traits, indicating the importance of additive and non- additive gene effects in the inheritance o traits. However, the ratio of σ2 gca/ σ2 sca was recorded below unity showed in the traits for days to blooming, plant height and spike length indicating the preponderance of non-additive type of gene actions for all these characters and reaming traits were showed high gca /sca ratio. The parents who were good general combiner for grain yield per plant were also good general combiners for some of its yield contributing traits. HD-2967 for yield, 1000 grain weight and days to maturity, PBW-154, K-9107, SUPER-111, RAJ-3765, UP-2338, K-7903 and PBW-502 were the good general combiners, it was interesting to note that K-7903 exhibited superior performance for grain yield per plan, whereas crosses HD-2967 × DPW-621-50, PBW-343× K-9107, PBW-343× PBW-154, and PBW-343 × PBW-502 were found to be best specific combiners for grain yield per plant  and some of the yield contributing traits were considered to be most promising for further exploitation in breeding programs.